2022
DOI: 10.1161/jaha.121.025364
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mitral Annulus Disjunction and Mitral Valve Prolapse in Patients With Idiopathic Ventricular Fibrillation

Abstract: Background Idiopathic ventricular fibrillation (IVF) is diagnosed in patients with ventricular fibrillation of which the origin is not identified after extensive evaluations. Recent studies suggest an association between mitral annulus disjunction (MAD), mitral valve prolapse (MVP), and ventricular arrhythmias. The prevalence of MAD and MVP in patients with IVF in this regard is not well established. We aimed to explore the prevalence of MAD and MVP in a consecutive cohort of patients with IVF comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…bileaflet MVP and MAD, which are more prevalent in women. 45 Indeed, in addition to greater global ECV%, women with arrhythmic MVP in our study exhibited greater “regionalized” interstitial fibrosis, specifically higher ECV% in the mid inferolateral LV, which was not observed in men. Altogether, these findings support the role of sex-specific factors in the development of myocardial fibrosis and subsequent risk of ventricular arrhythmia in MVP.…”
Section: Discussionmentioning
confidence: 40%
“…bileaflet MVP and MAD, which are more prevalent in women. 45 Indeed, in addition to greater global ECV%, women with arrhythmic MVP in our study exhibited greater “regionalized” interstitial fibrosis, specifically higher ECV% in the mid inferolateral LV, which was not observed in men. Altogether, these findings support the role of sex-specific factors in the development of myocardial fibrosis and subsequent risk of ventricular arrhythmia in MVP.…”
Section: Discussionmentioning
confidence: 40%
“…However, MAD by itself is a significant risk factor of arrhythmia. Groeneveld et al [47] research also support that hypothesis. In their study, they included 72 subjects with an IVF and 72 healthy controls.…”
Section: Madmentioning
confidence: 74%
“…Hence, Groeneveld et al re-evaluated CMR images to study the prevalence and morphology of mitral annulus disjunction (MAD) and MVP in a multicenter IVF cohort. Mitral valve abnormalities have been previously associated with UCA [ 67 , 68 ]. MAD is a structural abnormality in which the hinge point of the mitral valve is abnormally placed in the atrium [ 69 ].…”
Section: The Use Of Multiple Imaging Modalitiesmentioning
confidence: 99%
“…The study of Groeneveld et al revealed that inferolateral MAD and MVP were significantly more prevalent in IVF patients compared to healthy controls ( Figure 5 ). The authors recommended that MAD and MVP should deserve specific attention when evaluating UCA patients and showed the value of re-evaluating IVF patients based on the expanded medical knowledge during follow-up [ 67 ].…”
Section: The Use Of Multiple Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation